Explosive instability in the plasma-beam systems - Buts, V.A.; Koval’chuk, I.K. (Вопросы атомной науки и техники, 2012)
The results of investigation of explosive instability in the plasma-beam systems are presented. It has been shown that in the general case, the dynamics of this instability can be essentially changed, right up to its full suppression, if one takes into account a fast beam wave (wave with positive energy). The parameters when explosive instability is realized and when it is suppressed are defined. It was shown that in the case of such four wave interaction there are regimes with attributes of irregularity.